A randomized pilot of eHealth mindful movement and breathing to improve gynecologic surgery outcomes. Issue 3 (4th May 2023) - Sohl, Stephanie J.; Tooze, Janet A.; Levine, Beverly J.; Zeidan, Fadel; Wheeler, Amy; Kelly, Michael; Shalowitz, David; Danhauer, Suzanne C.
Abstract: Objective: To conduct a pilot randomized controlled trial of eHealth Mindful Movement and Breathing (eMMB) compared to an empathic attention control (AC). Participants: Women undergoing surgery for a suspected gynecologic malignancy. Methods: eMMB is a brief yoga intervention delivered remotely during the perioperative timeframe. We assessed feasibility and participants completed assessments (baseline, weeks 2 and 4 postoperatively). We summarized feasibility, participant characteristics, and outcomes by intervention group and time. Findings: Forty-three percent of eligible patients approached participated ( n = 31). Adherence to the interventions was 77%. Percent of participants to complete outcomes was 81% at Week 2 and 84% at Week 4 (>70%; retention was the primary feasibility indicator). Average reductions in the primary outcome of pain intensity were larger in the eMMB group than AC group (Week 2 d = −0.38; Week 4 d = −0.46). Implications: This pilot study of eMMB supported feasibility and improvements in pain intensity that warrant a future efficacy study.